Digital Dermatoscopy Method for Human Skin Roughness Analysis - Suprijanto Suprijanto; V. Nadhira; Dyah A. Lestari; E. Juliastuti; Sasanti T. Darijanto (Journal of ICT Research and Applications, 2011)
In this study we  propose a digital dermatoscopy  method to measure the human skin roughness. By using this method we eliminate the use of silicon replica.  Digital  dermatoscopy  consists  of  handheld  digital  microscope,  image processing  and  information  extraction  of  skin  roughness  level.  To  reduce  the noise due to the variation of reflection factor on the skin we use  median filter. Hence, by Fourier transform the skin texture is imaged in terms of 2D frequencyspatial  distribution.  Skin  roughness  is  determined  from  its  entropy,  where  the roughness level is proportional to the entropy.  Three types of experiment have been performed by evaluating: (i) the skin replicas; (ii)  young and elderly skin; and (iii) seven volunteers treated by anti wrinkle cosmetic in three weeks period. We find that for the first and second experiment that our system did manage to quantify the roughness, while on the third experiment, six of seven volunteers, the roughness are succeeded to identify.